2017
DOI: 10.1101/108217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Complex Dynamics of an Ion Channel Voltage Sensor Domain via Computation

Abstract: Voltage-gated ion channels are ubiquitous proteins that orchestrate electrical signaling across excitable membranes. Key to their function is activation of the voltage sensor domain (VSD), a transmembrane four alpha-helix bundle that triggers channel opening. Modeling of currents from electrophysiology experiments yields a set of kinetic parameters for a given channel, but no direct molecular insight. Here we use molecular dynamics (MD) simulations to determine the free energy landscape of VSD activation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…; Delemotte et al . ). Interestingly, the same work demonstrated a nearly 0 kcal mol −1 end‐point free energy difference when considering Δ Q as a reaction coordinate (Delemotte et al .…”
Section: Mechanisms Of Ion Channel Gatingmentioning
confidence: 97%
“…; Delemotte et al . ). Interestingly, the same work demonstrated a nearly 0 kcal mol −1 end‐point free energy difference when considering Δ Q as a reaction coordinate (Delemotte et al .…”
Section: Mechanisms Of Ion Channel Gatingmentioning
confidence: 97%
“…In a previous study, we reported five conformational states of the Kv1.2 VSD called E (resting), A (activated), and Δ , Γ , and B (intermediate states) ( 49 , 50 ). Here, we followed the provided checklist ( Box 1 ) and trained an RF classifier to compare these states and elucidate their defining structural elements using more than 12,000 frames from an enhanced sampling trajectory (see Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Snapshots corresponding to configurations making up five metastable states were extracted from a metadynamics trajectory taken from our previous study (48,49). The five states were previously identified using the network of salt bridges between the S4 positive residues and their negative counterparts as a collective variable (50).…”
Section: Vsd Analysismentioning
confidence: 99%
“…Instead, enhanced sampling was used, in the form of metadynamics simulations [148]. The set of collective variables that was used to enhance the sampling combined breaking and forming of salt bridges and the displacement of the voltage sensor’s charged residue along the pathway defined by binding partners [236]. When projected onto the gating charge reaction coordinate, the free energy landscape reveals that the activation sequence involves five metastable states that are organized in an early activation sequence with three low free energy barriers (~5 kcal/mol) and a late activation sequence involving a single high free energy barrier (~12 kcal/mol) (Figure 4.C).…”
Section: Key Questions Subject To Interdisciplinary Study In Ion Tmentioning
confidence: 99%
“…Note the three low free energy barriers in the early activation sequence (~5 kcal/mol) and the single high free energy barrier in the late activation sequence (~12 kcal/mol) (D) Comparison between gating currents obtained from kinetic modeling using the free energy landscape calculated by molecular dynamics simulations (black) and inferred from electrophysiology recordings (green). From [236], licensed under CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/). …”
Section: Figurementioning
confidence: 99%